Variations phonétiques du français chez de jeunes locuteurs de 15 à 19 ans dans une zone périurbaine en Algérie - Soufiane BENGOUA (My University, 2013)
It remains difficult to identify the characteristics of language use in an environment where multiple language practices coexist with each time variations observed. French in Algeria and among the different varieties of Arabic and Berber is an integral part of this landscape multi linguistic. Its use, each time changing, relevant to the present study on the socio-educational and socio-phonetic. Our method departs from the general progress during the work on the phonetic structure in Algeria. We focused our analysis by working on a variety of Arabic Algerian whose structure can not be compared to other varieties of Arabic. We are particularly interested a 09 sounds in 32 syllabic positions in perception and 31 positions in syllabic realization in one of the two phonetic structures of the mother tongue of 77 young speakers operating in a suburban area northwest of Algeria. Conditioning the realization by the perception and contrast the sounds of mother tongue with the sounds of the foreign language learning in the latter, led us to opt for the model SLM Flege James to consolidate our contrastive approach. After our work enshrined in its theoretical basis, we analyzed each sound perceived and performed correctly and incorrectly in a segment and a different position from each informant. We then crossed the so-called external variables (age, sex, geographic location, level of exposure to French) and analyzed social criteria to identify the origin of phonetic variation and the type of transfer lines articulatory , either infrastructural (within one and the same structure) or between structural (between two different structures). The results we have obtained have allowed us to develop the language of younger speakers and offer them an education that draws its resources from their phonetic prerequisites and whose objective is to regulate the phonetic variation in achievement and perception. This regulation is achieved through a systematic correction that builds and supports various educational activities as listening to songs, reading poetry, completed questionnaires and exercises to discrimination.